1994
DOI: 10.1192/bjp.164.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Australia Antigen (HBsAg) in Institutionalised Patients with Psychosis

Abstract: In a study of 100 institutionalised patients with psychosis and an equal number of age- and sex-matched healthy controls from the same regional background, the prevalence of Australia antigen (HBsAg) was 11 and 2, respectively. Institutionalised psychotic patients are a high-risk group for hepatitis B virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…HBV infection was slightly lower in females than males in our study, and this result agrees with that reported by Chang et al [12]. With respect to clinical diagnosis, risk groups for HBV infection include chronic schizophrenia patients [18], and institutionalized psychotic patients [19]. Nevertheless, frequencies of schizophrenia patients and psychotic patients were not statistically different in HBV positive and HBV negative patients of our study.…”
Section: Discussionsupporting
confidence: 91%
“…HBV infection was slightly lower in females than males in our study, and this result agrees with that reported by Chang et al [12]. With respect to clinical diagnosis, risk groups for HBV infection include chronic schizophrenia patients [18], and institutionalized psychotic patients [19]. Nevertheless, frequencies of schizophrenia patients and psychotic patients were not statistically different in HBV positive and HBV negative patients of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Although less research on hepatitis in psychiatric disorders has been carried out, studies from Jordan (45), India (46), USA (36), Italy (47), Turkey (48), and Japan (49) also showed an increased prevalence of hepatitis in people with schizophrenia compared to the general population.…”
Section: Resultsmentioning
confidence: 99%
“…Across different continents, markedly elevated rates of hepatitis virus infection have been reported in persons with SMI compared to the general population 364,396,397,398,399,400,401,402,403. The largest study to date found prevalence rates of hepatitis B virus (23.4%) and hepatitis C virus (19.6%) in SMI patients to be approximately 5 and 11 times the overall estimated population rates for these infections.…”
Section: Physical Diseases Linked To Smi And/or Psychotropic Treatmentmentioning
confidence: 99%